Understanding Girls 2016
DOI: 10.1007/978-94-6300-497-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Letting Girls Speak Out About Science

Abstract: The purpose of this study was to try to determine what influences girls to choose science. Forty girls were interviewed in Grades 2 , 5 , 8, 1 1 using a semistructured protocol. The interview focuscd on feelings about science, science careers, peer and parental support, and how science is taught. To determine whether their responses were based on gender, each girl was asked to respond to questions as if she were a boy. The girls were highly self-confident and positive about science. All of the girls took a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 26 publications
2
41
1
3
Order By: Relevance
“…The literature has also cited gender differences in STEM interest, which may be the product of gender-role socialization, in predicting women's participation in STEM. This may also be in part due to women's perception that STEM fields tend not to hold real life applications for societal impact (Baker and Leary 1995;Hill et al 2010;Sax 2001;Thompson and Windschitl 2002;Turner and Lapan 2005).…”
Section: Psychological Factors Values and Preferencesmentioning
confidence: 99%
“…The literature has also cited gender differences in STEM interest, which may be the product of gender-role socialization, in predicting women's participation in STEM. This may also be in part due to women's perception that STEM fields tend not to hold real life applications for societal impact (Baker and Leary 1995;Hill et al 2010;Sax 2001;Thompson and Windschitl 2002;Turner and Lapan 2005).…”
Section: Psychological Factors Values and Preferencesmentioning
confidence: 99%
“…Oloyede and Olatoye (2005) reported that there was no significant relationship between peer influence and study habit; peer influence did not predict study habit; peer influence accounted for 0.0% of the total variance in adolescents' study habits; there was no significant difference between male and female adolescents both in the levels of peer influence and study habit. Bolatito, Olugbemiro, and Oyebanji (2011) reported that a comprehensive review of the literature on gender differences reveals that the factors which have been found responsible for the gender imbalance in science could be grouped into six broad categories :individual factors (Baker & Leary, 1995); cognitive factors (Forrest, 1992); attitudinal factors (Catsambis, 1995); home and family factors (Simpson & Oliver, 1990); educational factors (Jegede & Okebukola, 1992). Intervention programme have been mounted in several parts of the world to engage more girls and women in science and science-related careers.…”
Section: Introductionmentioning
confidence: 99%
“…13 Especially women and minorities do not pursue a career in science even though they are talented because of the negative stereotypical image of a scientist. 14 General image of a scientist is "Einstein" model who is a white male with messy hair and lab coat on him. 15 That image could possibly discourage females and some males to pursue careers in science-related professions such as medical and engineering jobs.…”
Section: Di̇ş Heki̇mi̇ İle İlgi̇li̇ Si̇mgesel Genel Kani Ve Di̇ş Heki̇mli̇ği̇ Ementioning
confidence: 99%